Seleção de indicadores para gestão sustentável da olericultura em Itabaiana/SE - Souza, Danielle Thaís Barros de (2008)
Sustainable agriculture has been an increasing concern for the diverse involved social segments. The use of tools as indicating of sustainability in horticulture productive systems becomes important at a time that can contribute for the reduction of its ambient liabilities. This research had as objective generality to consider pointers of sustainability for horticulture producers in the city of Itabaiana in the State of Sergipe, in order to contribute for identification and monitor of the production systems. As specific objectives, the study aims to characterize the production systems and select pointers for sustainable management of the productive systems. It is a study of field of exploratory and descriptive type carried from half-structuralized interview with 28 proprietors of horticulture cultures of the city of Itabaiana - Sergipe, selected for being supplying of the Net of G Barbosa supermarkets. The pointers had been selected on the basis of the information collected and in the method considered for the United Nations Environment Program, known as Pressure / Estate/ Answer (P.E.A.). On the basis of the characterization of the production systems evidenced a series of problems that if observed for the optics of the sustainability present fragilities in the social, economic and ambient dimensions. 43 pointers of sustainability had been selected for the evaluation aiming to monitor which attributes of the activity may be contrary with the objectives.